Modeling the U.S. Federal Reserve Influence on Indonesia’s Interest Rates: A Markov-Switching Approach - Wibowo, Bintang Satrio; Mohammad Aulia Rachman; Ahmad Syahrul Fauzi; Abi Fadillah (Universitas Negeri Semarang, 2025)
This study aims to examine how changes in the United States’ monetary policy, such as interest rates and GDP, affect Indonesia’s economic policy, as reflected in Indonesia’s interest rate. The study employs the Markov Switching Dynamic Regression (MSDR) method to analyze these effects, using secondary data obtained from the Federal Reserve. This data includes variables for Indonesia’s and the United States’ interest rates, as well as other control variables. The results show that Indonesia’s interest rate, both in expansionary and contractionary conditions, tends to be influenced by the U.S. interest rate. In contrast, the U.S. GDP has no significant effect on Indonesia’s monetary policy. These findings suggest that external financial conditions, particularly those from the United States, have a significant impact on the economic situation of developing countries, including Indonesia.